Towards the formulation of the Malaysian housing policy - Mohd, Thuraiya; Alias, Buang (2008)
Housing development is an important essence in a nation development. The fundamental in a housing development sector is the housing policy undertaken by the government. The main objective of the housing policy as stated in the Malaysian Plan is to provide adequate, quality, affordable housing for all income groups and complete with full basic amenities. When we refer to affordable, adequate and quality houses, we should also focused on other factors that may have strong influence in achieving the Malaysian Plan set out by the government. These factors comprises of land availability, squatters settlements, overhang, unsold properties, poor workmanship and low quality of material, delay in delivery of houses, abandonment of housing projects, poor loan facilities; and the most important factor is the weak enforcement from all levels of the government department particularly at the state level and the local authorities. All these factors should be considered as major factors affecting the housing industry in Malaysia. Nevertheless, the Malaysian federal government has enacted laws to protect buyers and to regulate the standards and practices of the housing industry, but there is no specific law governing the housing industry in Malaysia. However, the private housing developers are governed by the Housing Developers (Control and Licensing) Act 1966, the Housing Developers (Control and Licensing (Amendment)) Act 1988 and the Housing Developers (Control and Licensing) Regulations 1989, which requires them to obtain licenses for advertising and sales permits from the Ministry of Housing and Local Government of Malaysia before they begin any housing projects with more than four housing units. Hence, this research emphasizes on identifying the existing Malaysian Housing Policy and focus into the various problems and issues of housing development in Malaysia such as unsold, overhang properties, oversupply, squatters’ settlement in the urban areas and abandoned projects. This paper will recommend new strategies and policies to be identified for the formulation of the National Housing Policy for Malaysia that will be the guidance to the housing industry as a whole.